Muslim Students' Preferences for Buddhist Universities: A Study of Inclusion Management in the Generation Z - Pringgondani; Franky Okto Bernando; Andhyka Wicaksono (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2026)
The phenomenon of a growing number of Muslim students who are studying in Buddhist-based universities has been a great special educational case in the multicultural condition of higher education in Indonesia. This research analyzes factors that Muslim students consider when selecting the Sriwijaya State Buddhist College (STABN) and how inclusive management is implemented to offer a friendly learning environment for interfaith students in the era of Generation Z. The method employed in this study is qualitative, approach by a phenomenologic method. Empirical evidence was gathered from Muslim students and institutional agents using interviews, observations and documents. Thematic analysis with the help of NVivo software was employed in data analysis. The finding indicates that the desire of Muslim students is shaped by rational and pragmatic considerations, namely tuition fees, scholarships, state university status, accessibility and academic quality. Furthermore, an open social climate, assured imperative free religion, offered worship opportunities and positive first experiences support the pupils' choices. Inclusivity in management at STABN Sriwijaya is shown by making non-discriminatory rules, academic freedom, interfaith programs and contribution of leaders as well as lecturers to the acts; however the written regulation has not been comprehensive. This study demonstrates that inclusive management is a strategic tool for fostering trust and comfort among interfaith students in higher education.